Performance of pre and post emergence herbicides on weed dynamics, yield and productivity of boro rice in red and lateritic soil of West Bengal: Bio- efficacy of herbicides in transplanted boro rice - PRAMANIK, KALIPADA; Gupta, Rahul Kumar; Ghosh, Pritam; Mahanti, Aparna; Bharti, Ruchi; Aktar, Sk Naim; Ram, Siya (ORYZA-An International Journal of Rice, 2025)
ABSTRACTThe effect of herbicides on weed suppression, crop growth and yield in transplanted rice were evaluated in at Agricultural Farm of Palli Siksha Bhavana, Visva-Bharati, Sriniketan during boro season of 2018 and 2019. Eight different weed management treatments comprised of pretilachlor 50 EC @ 500 g ha-1 and pyrazosulfuron ethyl 10 WP @ 30 g ha-1 as pre- emergence; ethoxysulfuron 15 WDG @ 15 g ha-1 and penoxsulam 21.7 SC @ 22.5 g ha-1 as early post emergence, bispyribac-sodium 10 SC @ 25 g ha-1 as post emergence, hand weeding at 20 and 40 DAT, weed free check and weedy check. Results revealed that pyrazosulfuron ethyl 30 at g ha-1 and pretilachlor at 500 g ha-1 resulted lower population and dry matter accumulation of weeds as well as increased plant height, dry matter accumulation, leaf area index and grain yield (6.09 and 5.99 t ha-1 in 2018 and 5.86 and 5.63 t ha-1 in 2019, respectively). Pretilachlor at 500 g ha-1 and pyrazosulfuron ethyl 30 at g ha-1 increased grain yield over other herbicidal treatments in both the years. The maximum loss of grain yield due to unrestrained weeds in transplanted summer rice was 55.85% and 52.3% in 2018 and 2019, respectively. Hand weeding done at 20 and 40 DAT also controlled weeds efficiently but recorded lower net return and return per rupee invested than pyrazosulfuron ethyl 30 at g ha-1 and pretilachlor at 500 g ha-1 where net return was higher (Rs. 94425 ha-1 and Rs. 92909 ha-1 in 2018; and Rs. 91206 ha-1 and Rs. 86926 ha-1 in 2019, respectively) and return per rupee invested (Rs. 3.64 and Rs. 3.63 in 2018; and Rs. 3.40 and Rs. 3.32 in 2019, respectively).